Fandom Communication And Participatory Culture In Digital Platforms: A Systematic Literature Review - Sena Luktridiansyah Pawelloi; Reza Safitri (INJECT (Interdisciplinary Journal of Communication), 2026)
This study aims to examine informal fandom as a form of interdisciplinary communication within digital media, synthesizing how participatory culture and platform-mediated fan practices have been conceptualized across the academic literature. The findings benefit scholars in communication science, media studies, and platform studies by providing an integrated analytical framework that bridges participatory culture theory, audience studies, and digital media research. This study employed a qualitative Systematic Literature Review method using three Boolean search strings on the Scopus database, limited to English-language peer-reviewed articles published between 2015 and 2026. Following PRISMA-based screening, 40 articles were included in the final thematic synthesis. Four analytical themes were identified: communicative community formation in digital fandom, participatory fan production as audience communication practice, platformed fan communication and digital labor, and contestation as communicative authority negotiation. A key tension identified is the contradiction between participatory communicative agency and platform power, including algorithmic visibility, datafication, and commercialization of fan communication. This review positions informal fandom as an analytical bridge within interdisciplinary communication scholarship, linking participatory culture theory, audience studies, and platform-mediated communicative practices. The findings contribute operational indicators for future empirical research on informal fandom, including loose affiliation, repeated digital interaction, affective attachment, platform-mediated visibility, participatory production, and symbolic meaning-making as measurable dimensions of audience communication in digital platforms.